Methamphetamine, Symbolic Boundaries, and Using Status. Issue 12 (2nd December 2017) - Webb, Megan; Deitzer, Jessica; Copes, Heith
ABSTRACT: Meth users construct symbolic boundaries by depicting themselves as functional users, while portraying other meth users as dysfunctional. Here, we compare the symbolic boundaries of women meth users who are in treatment to those who are not in treatment to determine if boundaries differ as a function of treatment status. We find that their accounts revealed mostly shared boundaries. However, we found differences in their boundaries related to using other drugs and their views of the morality of meth use. These findings indicate that people seek to distance themselves from stigmatized others, regardless of their current use status.